2022
DOI: 10.3390/ijms23105691
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Validation of the Therapeutic Potential of Dendrimer-Based Nanoformulations against Tumor Stem Cells

Abstract: Tumor cells with stem cell properties are considered to play major roles in promoting the development and malignant behavior of aggressive cancers. Therapeutic strategies that efficiently eradicate such tumor stem cells are of highest clinical need. Herein, we performed the validation of the polycationic phosphorus dendrimer-based approach for small interfering RNAs delivery in in vitro stem-like cells as models. As a therapeutic target, we chose Lyn, a member of the Src family kinases as an example of a promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…This surprising result suggested that the GSCs were specifically sensitive to PEI toxicity, which has been reported once in the literature recently by Prabhakar et al (2021) [ 46 ], who observed that PEI-coated silica nanoparticles presented a high level of toxicity which was seemingly selective to GSCs. A recent study by Knauer et al (2022) [ 47 ] also suggests greater toxicity of a dendrimeric cationic polymer towards GSCs when compared to U87 cells. This is of interest as the use of such polymers as carriers for drugs (as in our case) at concentrations to which non-CSCs are not sensitive, could provide a two-pronged approach for delivering drugs which are known to be effective against bulk tumour cells, while also having a carrier-dependent or linked effect against a polymer-sensitive CSC niche.…”
Section: Resultsmentioning
confidence: 99%
“…This surprising result suggested that the GSCs were specifically sensitive to PEI toxicity, which has been reported once in the literature recently by Prabhakar et al (2021) [ 46 ], who observed that PEI-coated silica nanoparticles presented a high level of toxicity which was seemingly selective to GSCs. A recent study by Knauer et al (2022) [ 47 ] also suggests greater toxicity of a dendrimeric cationic polymer towards GSCs when compared to U87 cells. This is of interest as the use of such polymers as carriers for drugs (as in our case) at concentrations to which non-CSCs are not sensitive, could provide a two-pronged approach for delivering drugs which are known to be effective against bulk tumour cells, while also having a carrier-dependent or linked effect against a polymer-sensitive CSC niche.…”
Section: Resultsmentioning
confidence: 99%
“…Dendrimers containing main group elements in the core or as branching points have demonstrated excellent chemical stability and good biocompatibility acceptable for biomedical applications. Polycationic dendrimers of phosphorus-based or silicon-based architecture have been shown to serve as efficient transporters of therapeutic oligonucleotide constructions [ 12 , 19 , 20 , 21 ]. Their unique characteristics permit to achieve the transfection of highly complex biological objects, namely immune cells—a highly heterogenous population including cell types known to be poorly transfectable by commonly used agents.…”
Section: Introductionmentioning
confidence: 99%
“…This work is a follow-on study which showed GSCs to present a specific sensitivity to the toxicity of 22 kDa L-PEI, which induced a necrosis-like, autophagy-inducing cell death with characteristics of immunogenic cell death [ 31 ]. Considering this and two recent reports in the literature which also indicated that GSCs were sensitive to polycation toxicity [ 25 , 26 ], we wished to investigate whether the observed effect was a phenomenon general to polycations. The results showed a higher level of toxicity towards GSCs than towards non-stem glioma cells for all of the polycations tested.…”
Section: Discussionmentioning
confidence: 99%
“…This seemed to occur through a necrosis accompanied by an induction of protective autophagy, which is an autophagic response to some chemotherapeutic insults, the inhibition of which may increase the sensitivity of the cells to the treatment [ 32 ]. In light of this result, and the two other studies which report a significant toxicity of PEI-coated nanoparticles [ 25 ] and a cationic phosphorous dendrimer [ 26 ] towards GSCs, we wished to elaborate this potentially important phenomenon. Thus, in this study, we evaluated the cytotoxicity of a range of cationic polymers varying in their size, type and topology towards the NCH421K (GSC) and U87-MG (non-stem glioma) cell lines.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation